The Role of Cultural Activities in Community Development - Baiba Tjarve; Ieva Zemīte (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
Culture has a critical role in transforming localities into more attractive places to work and invest. Cultural activities and facilities significantly affect the development of the physical environment of cities. But what does it all mean for the local residents of the neighbourhoods? How do they feel or participate in cultural activities organized for them? The overall aim of this study has been to evaluate participation effect on the development of Riga’s neighbourhoods during the year of The European Capital of Culture. During the research, the authors have used the mixed research methodology. The qualitative analysis of the Riga 2014 programme has been done based on the qualitative interviews with the artistic team, project managers and entrepreneurs from Riga’s neighbourhoods; besides, a detailed analysis of Riga 2014 programme events has been performed. The main findings show that cultural life in the neighbourhoods is among the most important factors determining the satisfaction with life by the neighbourhoods’ inhabitants. Personalities, not infrastructure have a crucial importance in the development of neighbourhood cultural life. Cultural activities in neighbourhood should be carried out in close cooperation with the stakeholders from different sectors. This can bring to sustainable and long‑term effects.